Psychometric evaluation of the Chinese version of the fear of pregnancy scale: a translation and validation study - Wu, Chunyan; Zhang, Jian; Zhao, Lei; Li, Yanhong; Yan, Yuanyuan; Wei, Yue; Zhang, Zhixia; Guo, Shuming (Frontiers in Public Health, 2024)
Introduction: Many women experience fear towards pregnancy, which can impact their desire to have children and the national birth rate. Thus, assessing women's fear of pregnancy is of great importance. However, there is currently no specialized tool for assessing women's fear of pregnancy in China. The purpose of this study is to translate the Fear of Pregnancy Scale into Chinese and test its reliability and validity among women of childbearing age. Methods: Using convenience sampling combined with a snowballing method, a crosssectional survey was conducted on 886 women of childbearing age in two cities in China. The translation was strictly carried out according to the Brislin model. Item analysis, validity analysis, and reliability analysis were employed for psychometric assessment. Results: The Chinese version of the Fear of Pregnancy Scale comprises 28 items. Exploratory factor analysis extracted four factors with a cumulative variance contribution rate of 72.578%. Confirmatory factor analysis showed: NFI = 0.956, CFI = 0.986, GFI = 0.927, IFI = 0.986, TLI = 0.985, RMSEA = 0.032, and χ2/df = 1.444. The scale's Cronbach's α coefficient is 0.957, split-half reliability is 0.840, and test-retest reliability is 0.932. Conclusions: The Chinese version of the Fear of Pregnancy Scale possesses robust psychometric properties and can assess the degree of pregnancy fear among Chinese women of childbearing age. It provides a reference for formulating relevant policies in the prenatal care service system and implementing targeted intervention measures.